Changing trends in nutritional status of adolescent females: a cross-sectional study from urban and rural Bangladesh - Subhasish Das; Tahmeed Ahmed; Soroar Hossain Khan; Ishita Mostafa; Mahamudul Hasan; Md Iqbal Hossain; Abu Faruque (BMJ Open)
Objectives Malnutrition remains a major problem among adolescents worldwide, but the types of nutritional problem impacting this group are changing significantly. This study aims to describe and analyse the trends in nutritional status and related epidemiological characteristics of 10 to 19 years old adolescent girls over time (2001 to 2018) in Bangladesh.Methods We extracted data from the Diarrhoeal Disease- Surveillance System of the International Centre for Diarrhoeal Disease Research Bangladesh. We performed χ2 test for trend to test for statistical significance of the changing trends of undernutrition and overnutrition among the study participants. Multivariable logistic regression model was fit to measure the strength of association, reported as adjusted OR (aOR) and corresponding 95% CIs.Results A total of 1224 and 628 adolescent females attended urban and rural treatment facilities, respectively, between 2001 and 2018. The proportion of stunting and thinness decreased substantially, whereas overweight has been observed to increase (1.7% to 7.4%, p<0.001) over the study period. Factors independently associated with stunting were illiteracy (aOR 2.39, 95% CI (1.68 to 3.39), p<0.001), monthly family income of less than US$100 (aOR 1.54, 95% CI (1.25 to 1.9), p<0.001) and family belonging to poorest wealth quintile (aOR 1.45, 95% CI (1.13 to 1.87), p=0.004). Younger participants (aOR 2.69, 95% CI (2.10 to 3.45), p<0.001), rural participants (aOR 1.71 95% CI (1.23 to 2.38), p<0.001), longer hospital stay (aOR 1.52, 95% CI (1.16 to 1.98), p=0.002) and monthly family income less than US$100 (aOR 1.44, 95% CI (1.09 to 1.89), p=0.009) were significantly associated with thinness. Conversely, overweight/obesity was associated with monthly family income more than US$100, duration of diarrhoea and rural participants.Conclusion Undernutrition in adolescent girls has decreased with time, but the burden of overweight has increased. Higher literacy and better wealth status were found to be associated with the improved nutritional status of the participants.